Photovoice: Exploring the Role of Teacher’s Question for University Students’ Fluency in Speaking Class - Nur Arifah Drajati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Abstract. Speaking skill is essential in language learning and teaching process because the goal of learning a foreign language is to be able to communicate using the target language. Fluency is one of the leading criteria that the students should accomplish in speaking skill. However, most of EFL students tend to be more nervous if they speak English, and this will impact their fluency. The objective of the research is to investigate how questioning gives an impact for students’ fluency in academic speaking class. The researchers used narrative inquiry to collect and process the data using Photovoice. The participants of this research were 12 university students. The finding shows that the use of questioning can develop students’ speaking fluency in academic speaking class. As the implication, teachers can give questions followed with feedback to enhance the students’ fluency. Keywords: fluency, speaking skill, questioning, photovoice.